Exciton formation in dye doped OLEDs using electrically detected magnetic resonance - Batagin-Neto, Augusto [UNESP]; Gomez, Jorge A.; Castro, Fernando A.; Nueesch, Frank; Zuppiroli, Libero; Graeff, Carlos Frederico de Oliveira [UNESP] (Spie - Int Soc Optical Engineering, 2011)
Electrically Detected Magnetic Resonance (EDMR) was used to investigate the influence of dye doping molecules on spin-dependent exciton formation in Aluminum (III) 8-hydroxyquinoline (Alq(3)) based OLEDs with different device structures and temperature ranges. 4-(dicyanomethylene)-2-methyl-6-{2-[(4-diphenylamino-phenyl]ethyl}-4H-pyran (DCM-TPA) and 5,6,11,12-tetraphenylnaphthacene (Rubrene) were used as dopants. A strong temperature dependence have been observed for doped OLEDs, with a decrease of two orders of magnitude in EDMR signal for temperatures above similar to 200 K. The signal temperature dependence were fitted supposing different spin-lattice relaxation processes. The results suggest that thermally activated vibrations of dopants molecules induce spin pair dissociation, reducing the signal.
Keywords: Alq3; dye doped OLEDs; DCM-TPA; Rubrene; EDMR; spin-relaxation processes